2012
DOI: 10.1038/labinvest.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

WNT3A induces a contractile and secretory phenotype in cultured vascular smooth muscle cells that is associated with increased gap junction communication

Abstract: Evidence suggests a role for Wnt signaling in vascular wound repair and remodeling events. Despite this, very little is known about the effect of Wnt ligands on the structure and function of vascular cells. In this study, we treated vascular smooth muscle cells with 250 ng/ml of recombinant Wnt3a for 72 h and observed changes in the cell phenotype. Our data suggest Wnt3a completely alters the phenotype of vascular smooth muscle cells. The Wnt3a-treated cells appeared larger and had increased formation of stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
5
22
0
Order By: Relevance
“…28,47,48 Likewise, endosialin has been found to promote atherosclerosis through phenotypic remodeling of vascular SMCs. 31 In accord with CXCL12 driving WNT signaling, we confirmed that both CXCL12 and WNT3a promoted the contractile phenotype of SMCs in vitro , 49 consistent with our observations upon Cxcr4 -deficiency in vivo . Combined with a reduced macrophage cholesterol efflux capacity due to lower ApoA1 serum levels, this may underlie atherogenic effects of Cxcr4 -deficiency in SMCs.…”
Section: Discussionsupporting
confidence: 88%
“…28,47,48 Likewise, endosialin has been found to promote atherosclerosis through phenotypic remodeling of vascular SMCs. 31 In accord with CXCL12 driving WNT signaling, we confirmed that both CXCL12 and WNT3a promoted the contractile phenotype of SMCs in vitro , 49 consistent with our observations upon Cxcr4 -deficiency in vivo . Combined with a reduced macrophage cholesterol efflux capacity due to lower ApoA1 serum levels, this may underlie atherogenic effects of Cxcr4 -deficiency in SMCs.…”
Section: Discussionsupporting
confidence: 88%
“…Gal-3 can also induce the migration of macrophage in mouse (27). Atherosclerosis is characterized by the activation and accumulation of smooth muscle cells in the intimal layer of blood vessels where they internalized a lot of lipids (28). The enhanced proliferation and migration of smooth muscle cells are the symbol of the early pathology of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…fibronectin, laminin, collagen) was downregulated, and the majority of these genes, especially those encoding Ar, α-SMA and fibronectin, have been reported as downstream targets of Wnt/β-catenin signaling (Carthy et al, 2012;De Langhe et al, 2005;Gradl et al, 1999;Hlubek et al, 2001;Yang et al, 2002;Yang et al, 2006). We speculated that Wnt/β-catenin signaling is functioning in PMCs and that the activity of this pathway is impaired in Lgr4 mutant PMCs, as Lgr4 has recently been demonstrated to be one of the receptors for R-spondins, which amplify Wnt signaling (Carmon et al, 2011;de Lau et al, 2011;Glinka et al, 2011;Hao et al, 2012).…”
Section: Lgr4 Modulates Wnt/β-catenin Signaling In Pmcsmentioning
confidence: 99%